A Pilot Study to Explore Novice Debriefers' Post-Simulation Debriefing Experiences. (August 2021) - Ng, Grace; Lugassy, Daniel M.
Introduction: Effectivedebriefing of simulation-based experiences is critical for learning. Approximately 33% of health professions instructors aredebriefing novices. However, specific faculty development needs of novicedebriefers has not been studied. This study examines how health professions instructors approachdebriefing when they are new todebriefing simulation-based experiences. Methods: This pilot qualitative study used a thematic analysis approach to explore novice debriefers' experiences in conducting post-simulation debriefings. Eligible participants engaged in one-hour semi-structured interviews. Recruitment continued until data saturation was reached. We reviewed verbatim interview transcripts, hand-coded the data, and formed codes into themes. Results: Nine novicedebriefers participated. The overarching theme "I'm on my own…and they're on their own, " reflectsdebriefers ' view that they are on their own, without resources.Debriefers also believe learners should identifying their own errors. Three main themes emerged: "Deep divide between me and the learners" portrays a separation betweendebriefers and learners in terms of expectations, roles, and responsibilities. "Winging it" depictsdebriefers ' making-up their owndebriefing approaches. "Debriefing quality: missing pieces of the puzzle" portrays novicedebriefers unaware of criteria for effectivedebriefing . Conclusions: Novicedebriefers in this study perceived that they were on their own, having little to nodebriefing training and mentorship. Study participants expresseddebriefing struggles in several areas including discussing errors, facilitating learner participation, and assessingdebriefing quality. Our findings shed light onsimulation as a growing specialty by health profession educators and it is critical that resources are devoted to faculty development fordebriefing skill acquisition . These findings can serve as a basis for future studies on debrieferskill acquisition .